2019
DOI: 10.1186/s13148-019-0704-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and epigenomic predictors of response to guadecitabine in relapsed/refractory acute myelogenous leukemia

Abstract: Background Guadecitabine is a novel DNA methyltransferase (DNMT) inhibitor with improved pharmacokinetics and clinical activity in a subset of patients with relapsed/refractory acute myeloid leukemia (r/r AML), but identification of this subset remains difficult. Methods To search for biomarkers of response, we measured genome-wide DNA methylation, mutations of 54 genes, and expression of a panel of 7 genes in pre-treatment samples from 128 patients treated at therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…On the one hand, clinical trials and clinically approved DNMTis are mostly applicable to hematological tumors. In addition to decitabine, which is often mentioned above, there is guadecitabine for the treatment of relapsed/refractory AML [ 125 ], and the combination of DNMTi CC-486 and HDACi romidepsin for the treatment of advanced solid tumors [ 126 ]. These drugs are also very promising in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, clinical trials and clinically approved DNMTis are mostly applicable to hematological tumors. In addition to decitabine, which is often mentioned above, there is guadecitabine for the treatment of relapsed/refractory AML [ 125 ], and the combination of DNMTi CC-486 and HDACi romidepsin for the treatment of advanced solid tumors [ 126 ]. These drugs are also very promising in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested the need for age-tailored targeted therapies for the treatment of pediatric AML [98]. Furthermore, a novel DNMT inhibitor, guadecitabine demonstrated improved pharmacokinetics and clinical activity in a subset of R/R AML patients [5].…”
Section: Dnmt3amentioning
confidence: 99%
“…Six genes, including FMSlike tyrosine kinase 3 (FLT3), nucleophosmin 1 (NPM1), CCAAT/enhancer binding protein alpha (CEBPA), Runtrelated transcription factor 1 (RUNX1), additional sex combs-like 1 (ASXL1), and tumor protein p53 (TP53), have already been incorporated into the risk categories proposed by the European Leukemia Net (ELN) [2]. Other recurrent gene mutations have been reported in AML patients [3][4][5][6][7][8]. Furthermore, the important roles of recurrent gene mutation in AML pathogenesis had been explored and gene mutation-targeted therapies had been developed [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, no predictive marker of response to guadecitabine has been defined for newly diagnosed AML. However, Chung et al reported no significant association between gene mutations and complete remission in a cohort of 128 relapsed/refractory AML [27]. Trends were observed for TET2 -mutated cases (higher CR rate) and IDH1/2 -mutated and TP53 -mutated AML (resistance).…”
Section: Resultsmentioning
confidence: 99%